The Regulatory Mechanisms and Clinical Significance of Lnc SNHG4 in Cancer - Pourghasem, Navid; Ghorbanzadeh, Shadi; Nejatizadeh, Abdol A. (Current Pharmaceutical Design, 2022)
Background: LncRNAs have been reported to be involved in a variety of biological functions, including gene expression, cell growth, and differentiation. They may also serve as oncogenes or tumor suppressor genes in diseases. lncRNAs that can encode small nucleolar RNAs (snoRNAs) have been named small nucleolar RNA host genes (SNHGs). Objective: In this review article, we readily review the regulatory mechanisms and clinical significance of Lnc SNHG4 in cancer. Methods: We systematically investigated databases, like Scopus, PubMed, Embase, Google Scholar, and Cochrane Library database for all research articles, and have provided an overview regarding the biological functions and mechanisms of lncRNA SNHG4 in tumorigenesis. Results: Compared to neighboring normal tissues, SNHG4 is significantly dysregulated in various tumor tissues. SNHG4 upregulation is mainly associated with advanced tumor stage, tumor size, TNM stage, and decreased overall survival. In addition, aberrant SNHG4 expression promotes cell proliferation, metastasis, migration, and invasion of cancer cells. Conclusion: SNHG4 may serve as a new therapeutic target and prognostic biomarker in patients with cancer.
Keywords: lncRNAs